The tales of Beedle the Bard - Rowling, J. K. (Children's High Level Group Bloomsbury, 2008)
A collection fairy tales for young wizards and witches. Each story is followed by observations on Wizarding history, personal reminiscences, and information on the story's key elements by Hogwarts headmaster, Albus Dumbledore.